Factors influencing knowledge and practice of self-medication among college students of health and non-health professions - Mitra, Amal K; Imtiaz, Ayyub; Al Ibrahim, Yusuf A; Bulbanat, Mohammad B; Mutairi, Maha F Al; Musaileem, Sulaiman F Al (IMC Journal of Medical Science, 2019)
Background and objectives: Self-medication is commonly practiced throughout the world. The aim of this study was to ascertain the use prevalence and knowledge of harmful effects of selfmedication among college students of health professions and non-health professions. Methods: A cross-sectional study was performed among 1,167 students from 12 faculties of a public university and two private universities in Kuwait. Data were collected using a selfadministered pretested questionnaire containing 32 questions. Results: Among the participants, 70.4% (822/1,167) used self-medication. The prevalence of self-medication was significantly higher among students of non-health professions compared with those of health professions (35.9% vs. 25.9%, p = 0.004, 95% CI, 6.28% to 13.73%, respectively). Pain killer medicines (52.9%), vitamins/minerals (13.1%), and antihistamines (9.0%) were the most commonly used non-prescription medications. Antibiotics and sleeping pills were used without a prescription in 2.9% and 2.1%, respectively. Older age, non-Kuwaiti national, and students of 5th to 7th year of study were significant predictors of self-medication. Knowledge scores of harmful effects of self-medication were about two-fold higher among females than their male counterparts. Similarly, students of higher years of study (5th to 7th year) had higher knowledge score compared with others. Conclusions: The prevalence of self-medication was alarmingly high among young adults in Kuwait. People should be informed about adverse effects of self-medication through mass and social media campaign. IMC J Med Sci 2018; 12(2): 57-68